Carbon Capture Usage and Storage with Scale-up: Energy Finance through Bricolage Deploying the Co-integration Methodology - Gupta, Bhumika; Sen, Salil K. (International Journal of Energy Economics and Policy, 2019)
Recent studies surprisingly indicate that fossil fuels could constitute 81 percent of primary energy demand, to 2040, 60 percent would continue to be from coal. This could mean more greenhouse emissions. This paper addresses the research proposition that coal though black, yet, could be green with co-integration of carbon capture & storage (CCS) and carbon capture & usage (CCU). The incertitude surrounding the future of coal is a palpable and credible research gap. The other research chasm is the search of energy finance necessary to economically, societally and environmentally leverage the carbon removal. This issue is addressed as bricolage finance for optimal resource optimization. The bricolage supports societal entrepreneurialism that deploy funding sources from bottom-up developmental finance. The twin key outcomes here are: (i) appropriately scaled-up, grassroots-sourced bricolage sustains the societal acceptance of CCS & CCU, (ii) enhances the environmental economics of coal-based thermal power plugged-in with CCU and CCS. The methodological essence of this approach is tri-trajectory literature review, that propose (i) technology-led CCU/CCS (ii) financial derivative based bricolage and (iii) economic recalibration through bottom-up approach for community-level buy-in. Practical application of this framework is probed with instances from less developed regions in Asia, Africa and Latin America. The data draws from published reports on coal-intensive habitats, particularly in developing countries. Pattern coefficients and reflective indicators were deployed to predict, monitor, and reorient support or opposition for CCS implementation. Keywords: energy finance through bricolage; carbon capture and usage; carbon capture and storage; pattern coefficients; reflective indicators JEL Classifications: Q01, O35, R580 DOI: https://doi.org/10.32479/ijeep.8104